Neodymium-iron-boron permanent magnet and preparation method and application thereof

By forming a dual-resistant film layer composed of organosiloxane and specific nanoparticles on the surface of the NdFeB permanent magnet, the problems of permeability and insufficient antibacterial properties of NdFeB permanent magnet are solved, and excellent anticorrosion and antibacterial properties are achieved, and the service life of the magnet is extended.

CN119601366APending Publication Date: 2025-03-11TIANJIN SANHUAN LUCKY NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411798568.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Neodymium-FeB permanent magnets are prone to rust and corrosion due to their loose surface porous and porous and extremely active neodymium-rich phases, and have put forward strict requirements on antibacterial properties in the fields of humanoid robots.

Method used

The NdFeB permanent magnet is used with a dual-resistant film layer. The film layer is composed of organosiloxane, specific nanoparticles and curing agent. A uniform film layer is formed through a three-stage curing process, which has anti-corrosion and antibacterial properties.

Benefits of technology

It realizes excellent anticorrosion and antibacterial properties of NdFeB permanent magnets, extends the use cycle of magnets, and is suitable for batch surface treatment of different sizes and shapes.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a neodymium-iron-boron permanent magnet and a preparation method and application thereof. The neodymium-iron-boron permanent magnet comprises a neodymium-iron-boron base body and a double-resistance film layer arranged on the surface of the neodymium-iron-boron base body. The preparation raw materials of the double-resistance film layer comprise organosiloxane, nanoparticles and a curing agent; the nano-particles comprise any one or a combination of at least two of titanium dioxide nano-particles, silver nano-particles, silver-titanium dioxide composite nano-particles, zinc oxide nano-particles and cerium oxide nano-particles. Organosiloxane and specific nanoparticles are introduced into the film layer of the neodymium-iron-boron permanent magnet, so that the film layer realizes inactivation of bacteria adhered to the surface of the film layer on the basis of having a traditional anti-corrosion function, and the neodymium-iron-boron permanent magnet has anti-corrosion and antibacterial characteristics; compared with electroplating nickel and other plating layers used by a traditional neodymium-iron-boron permanent magnet, the film layer provided by the invention has more excellent corrosion resistance and more excellent environment-friendly characteristic, and the magnetic performance of the neodymium-iron-boron permanent magnet is not influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of permanent magnets, and relates to a neodymium iron boron permanent magnet, a preparation method and uses thereof, and in particular to a neodymium iron boron permanent magnet with a double-resistance film layer, a preparation method and uses thereof. Background Art

[0002] Sintered NdFeB permanent magnets have been widely used in high-tech fields such as wind power generation, aerospace, communications, transportation, home appliances and humanoid robots due to their excellent comprehensive magnetic properties. However, due to the loose and porous surface of NdFeB permanent magnets and the highly active neodymium-rich phase, NdFeB permanent magnets are very prone to rust and corrosion, so they need to be treated with surface anti-corrosion. At present, conventional surface anti-corrosion treatment methods can be divided into: electroplating, chemical plating, chemical conversion film, electrophoresis and vacuum plating, etc., to obtain metal or alloy film layers, polymer coatings, chemical conversion film layers and composite coatings.

[0003] The metal materials used in humanoid robots include a large number of neodymium iron boron permanent magnets, and humanoid robots will be widely present in human life, especially in the medical field, which puts strict requirements on the antibacterial properties of the metal materials used in humanoid robots.

[0004] Therefore, there is an urgent need in the art to develop a NdFeB permanent magnet whose surface film layer has both corrosion resistance and antibacterial properties. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a NdFeB permanent magnet and a preparation method and use thereof, and specifically to provide a NdFeB permanent magnet with a dual-resistance film layer and a preparation method and use thereof.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a NdFeB permanent magnet, comprising a NdFeB matrix and a dual-resistance film layer disposed on the surface of the NdFeB matrix;

[0008] The raw materials for preparing the dual-resistance film layer include organic siloxane, nanoparticles, and a curing agent;

[0009] The nanoparticles include any one of titanium dioxide nanoparticles, silver nanoparticles, silver-titanium dioxide composite nanoparticles, zinc oxide nanoparticles, and cerium oxide nanoparticles, or a combination of at least two of them.

[0010] Compared with traditional NdFeB permanent magnet coatings, the present invention introduces organic siloxane and specific nanoparticles into the film layer of the NdFeB permanent magnet, so that the film layer can inactivate bacteria adhering to the surface of the film layer on the basis of having traditional anti-corrosion functions, and has anti-corrosion and antibacterial properties; compared with electroplated nickel and other coatings used in traditional NdFeB permanent magnets, the film layer provided by the present invention has better anti-corrosion performance, more excellent environmental protection characteristics and does not affect the magnetic properties of the NdFeB permanent magnet.

[0011] In the present invention, the metal silver nanoparticles are selected mainly because of their strong bactericidal ability. A certain proportion of silver nanoparticles can be used without significantly affecting the insulation of the coating.

[0012] In the present invention, the above-mentioned metal oxide nanoparticles are selected to meet the antibacterial properties while avoiding the introduction of nano metal oxide particles into the organosiloxane to reduce the film resistance; the non-conductive film layer can help protect the magnetic properties of the magnet; if the film layer is conductive, it will interfere with the magnetic field distribution of the NdFeB permanent magnet, and the use of metal oxides can effectively protect the stability of the magnetic properties.

[0013] Preferably, based on the total mass of the raw materials for preparing the dual-resistance film layer being 100%, the amount of the nanoparticles used is 2% to 6%, for example, 2%, 3%, 4%, 5% or 6%.

[0014] Preferably, the mass ratio of the organosiloxane to the curing agent is (9-15):1, for example, it can be 9:1, 9.5:1, 10:1, 10.5:1, 11:1, 11.5:1, 12:1, 12.5:1, 13:1, 13.5:1, 14:1, 14.5:1, or 15:1, etc.

[0015] Preferably, the titanium dioxide nanoparticles are anatase nanoparticles, which have excellent photocatalytic activity, can form active oxygen on the surface under natural light or ultraviolet light, and can oxidize most organic matter, thus having good bactericidal properties.

[0016] Preferably, the nanoparticles include silver-titanium dioxide composite nanoparticles or a combination of titanium dioxide nanoparticles and silver nanoparticles in a mass ratio of 9:1 to 7:3 (e.g., 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 7:3, etc.), a combination of titanium dioxide nanoparticles and zinc oxide nanoparticles in a mass ratio of 9:1 to 1:9 (e.g., 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, etc.), a silver nanoparticle in a mass ratio of 1:9 to 3:7 (e.g., 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 3:7, etc.). Any combination of a combination of particles and zinc oxide nanoparticles, a combination of titanium dioxide nanoparticles and cerium oxide nanoparticles in a mass ratio of 9:1 to 1:9 (for example, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, etc.), a combination of titanium dioxide nanoparticles in a mass ratio of 3:4:3 to 7:2:1 (for example, 3:4:3, 1:1:3, 5:3:2, 7:2:1, etc.), and a combination of zinc oxide nanoparticles and silver nanoparticles; further preferred are silver-titanium dioxide composite nanoparticles or a combination of titanium dioxide nanoparticles and cerium oxide nanoparticles in a mass ratio of 9:1 to 1:9.

[0017] As the preferred technical solution of the present invention, silver-titanium dioxide composite nanoparticles are preferably selected. The introduction of silver nano-ions can reduce the separation of electrons and holes in titanium dioxide nanoparticles, and can effectively improve the photocatalytic efficiency and antibacterial properties of the composite antibacterial nanoparticles.

[0018] As a preferred technical solution of the present invention, nanoparticles of a composite of cerium oxide and titanium dioxide (or a combination of cerium oxide nanoparticles and titanium dioxide nanoparticles) are preferably selected. Doping cerium oxide into titanium dioxide nanoparticles can effectively reduce the titanium dioxide grain size, inhibit the conversion of titanium dioxide nanoparticles from anatase to rutile, and the antibacterial effect is enhanced with the increase of cerium oxide content.

[0019] Preferably, the average particle size (D50) of the nanoparticles is 100-500 nm, for example, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, etc.

[0020] Preferably, the organosiloxane includes at least two of polydimethylsiloxane, phenylmethyl-dimethylsiloxane, and cyclopolydimethylsiloxane. The present invention adds at least two specific organosiloxanes, so that the film layer has excellent anti-corrosion performance and can effectively reduce the manufacturing cost; in addition, compared with a single polydimethylsiloxane, the introduction of phenylmethyl-dimethylsiloxane or cyclopolydimethylsiloxane can accelerate the formation of new silicon-oxygen bonds and the curing speed during the curing process, and the cross-linked structure formed by multiple organosiloxanes is more durable and wear-resistant.

[0021] Preferably, the organosiloxane includes any one of a combination of polydimethylsiloxane and phenylmethyl-dimethylsiloxane in a mass ratio of 3:2 to 4:1 (for example, 3:2, 2:1, 3:1, 4:1, etc.), a combination of polydimethylsiloxane and cyclopolydimethylsiloxane in a mass ratio of 4:1 to 1:4 (for example, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, etc.), a combination of cyclopolydimethylsiloxane and phenylmethyl-dimethylsiloxane in a mass ratio of 5:1 to 4:1 (for example, 5:1, 4.8:1, 4.5:1, 4.3:1, 4:1, etc.), and a combination of polydimethylsiloxane, phenylmethyl-dimethylsiloxane and cyclopolydimethylsiloxane in a mass ratio of 6:1:3 to 8:1:1 (for example, 6:1:3, 7:1:2, 6:1:2, 8:1:1, etc.).

[0022] Preferably, the curing agent includes any one of diphenyl butyl carbamate, dihydropropane peroxide, diisopropylbenzene peroxide, ethoxylated trimethylolpropane triacrylate, and dibutyl tin dilaurate, or a combination of at least two thereof.

[0023] Preferably, the thickness of the double-resistance membrane layer is 5 to 25 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, etc.

[0024] Preferably, the salt spray resistance test duration of the dual-resistance film layer is ≥480h, for example, it can be 480h, 490h, 500h, 520h, 550h, 600h, 650h or 700h, etc.

[0025] Preferably, the high-pressure accelerated aging life test duration of the dual-resistance film layer is ≥150h, for example, it can be 150h, 160h, 170h, 180h, 190h, 200h, 220h, 250h, 300h, 350h or 400h, etc.

[0026] Preferably, the antibacterial rate of the dual-resistance film layer is greater than 99%, for example, it may be 99.2%, 99.3%, 99.5%, 99.8% or 99.9%.

[0027] In a second aspect, the present invention provides a method for preparing the NdFeB permanent magnet as described in the first aspect, the preparation method comprising the following steps:

[0028] (1) mixing organosiloxane, nanoparticles, a curing agent and an organic solvent, and heating to obtain a mixed solution;

[0029] (2) coating the mixed solution on the surface of the NdFeB substrate and performing three-stage curing to obtain the NdFeB permanent magnet;

[0030] The three stages of curing are all heat treatment curing, including first stage curing, second stage curing, and third stage curing, wherein the temperature of the first stage curing is 50-70°C (for example, 50°C, 55°C, 60°C, 65°C, 70°C, etc.), and the curing time is 0.5-2h (for example, 0.5h, 1h, 1.5h, 2h, etc.); the temperature of the second stage curing is 80-100°C (for example, 80°C, 85°C, 90°C, 95°C, 100°C, etc.), and the curing time is 0.5-2h (for example, 0.5h, 1h, 1.5h, 2h, etc.); the temperature of the third stage curing is 100-140°C (for example, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, etc.), and the curing time is 1-2h (for example, 1h, 1.5h, 2h, etc.).

[0031] In the preparation method provided by the present invention, by adopting a staged temperature increase method to perform three-stage curing, the rate of the organic siloxane cross-linking chemical reaction can be slowed down, the degree of organic siloxane cross-linking can be increased, and the film layer can be quickly and completely cured; at the same time, the process can maintain the uniform dispersion of nanoparticles in the film layer, improve the overall uniformity of the film layer after curing, and reduce surface defects of the film layer.

[0032] The preparation method provided by the invention is simple, highly practical and easy to promote.

[0033] Preferably, the organic solvent includes any one of acetone, n-ethane, n-heptane, methanol, and styrene, or a combination of at least two thereof.

[0034] Preferably, the mixing in step (1) comprises first mixing the organosiloxane with the organic solvent for a first time to obtain a first system, then adding nanoparticles to the first system for a second mixing to obtain a second system, and then adding a curing agent to the second system for a third mixing.

[0035] Preferably, the first mixing method includes magnetic stirring.

[0036] Preferably, the speed of magnetic stirring in the first mixing is 150-220 rad / min, for example, 150 rad / min, 160 rad / min, 170 rad / min, 180 rad / min, 190 rad / min, 200 rad / min, 210 rad / min or 220 rad / min.

[0037] Preferably, the first mixing time is 1 to 2 hours, for example, 1 hour, 1.5 hours or 2 hours.

[0038] Preferably, the second mixing method includes magnetic stirring and ultrasound performed sequentially.

[0039] Preferably, the speed of magnetic stirring in the second mixing is 150-220 rad / min, for example, 150 rad / min, 160 rad / min, 170 rad / min, 180 rad / min, 190 rad / min, 200 rad / min, 210 rad / min or 220 rad / min.

[0040] Preferably, the duration of magnetic stirring in the second mixing is 5 to 20 min, for example, 5 min, 8 min, 10 min, 13 min, 15 min, 18 min or 20 min.

[0041] Preferably, the power of the ultrasound in the second mixing is 65-75 KHz, for example, 65 KHz, 68 KHz, 70 KHz, 73 KHz or 75 KHz.

[0042] Preferably, the duration of ultrasound in the second mixing is 5 to 20 min, for example, 5 min, 8 min, 10 min, 13 min, 15 min, 18 min or 20 min.

[0043] Preferably, the third mixing method includes magnetic stirring.

[0044] Preferably, the speed of magnetic stirring in the third mixing is 150-220 rad / min, for example, 150 rad / min, 160 rad / min, 170 rad / min, 180 rad / min, 190 rad / min, 200 rad / min, 210 rad / min or 220 rad / min.

[0045] Preferably, the duration of the third mixing is 0.5 to 1 h, for example, 0.5 h, 0.6 h, 0.8 h or 1 h.

[0046] Preferably, the heating temperature in step (1) is 40-50°C, for example, 40°C, 43°C, 45°C, 48°C or 50°C, and the heating time is 0.5-1h, for example, 0.5h, 0.6h, 0.8h or 1h.

[0047] Preferably, the coating in step (2) comprises spraying.

[0048] Preferably, the gas used for spraying includes air and / or nitrogen.

[0049] Preferably, the angle of the spray gun during the spraying is in the range of 15° to 40°, for example, 15°, 20°, 25°, 30°, 35° or 40°.

[0050] Preferably, the spraying distance is 25 to 35 cm, for example, it may be 25 cm, 27 cm, 29 cm, 30 cm, 32 cm, 34 cm or 35 cm.

[0051] Preferably, the spraying pressure is 100-160 psi, for example, it may be 100 psi, 105 psi, 110 psi, 115 psi, 120 psi, 125 psi, 130 psi, 135 psi, 140 psi, 145 psi, 150 psi, 155 psi or 160 psi, etc.

[0052] Preferably, before the coating in step (2), the process further comprises: sequentially degreasing, pickling and drying the surface of the NdFeB substrate. The degreasing and pickling processes can remove the oxide layer on the surface of the NdFeB substrate.

[0053] Preferably, the degreasing agent used in the degreasing treatment includes any one of sodium hydroxide, sodium carbonate, sodium bicarbonate or potassium hydroxide, or a combination of at least two of them.

[0054] Preferably, the degreasing treatment time is 3 to 15 minutes, for example, it can be 3 minutes, 5 minutes, 8 minutes, 10 minutes, 13 minutes or 15 minutes.

[0055] Preferably, the acid used for pickling includes any one of hydrochloric acid, nitric acid and sulfuric acid.

[0056] Preferably, the pickling time is 30 to 100 s, for example, 30 s, 40 s, 50 s, 60 s, 70 s, 80 s, 90 s or 100 s.

[0057] Preferably, the drying temperature is 80-120°C, for example, 80°C, 90°C, 100°C, 110°C or 120°C.

[0058] It should be noted that the present invention does not impose any specific limitation on the amount of the organic solvent, as long as it can evenly mix the organosiloxane, nanoparticles and curing agent, and the obtained mixed solution is convenient for subsequent coating.

[0059] In a third aspect, the present invention provides a use of the NdFeB permanent magnet as described in the first aspect, wherein the NdFeB permanent magnet is used in medical treatment, aerospace, transportation, household appliances or humanoid machines.

[0060] NdFeB permanent magnets are used in the field of humanoid robots at the medical level. On the basis of ensuring that the corrosion resistance of NdFeB permanent magnets meets the standards, due to the particularity of the application field, the coating on the surface of the NdFeB substrate must also have antibacterial properties. Based on the above needs, the present invention provides a corrosion-resistant and antibacterial dual-resistant coating, which meets the above needs by doping nano-antibacterial materials in organic silicone. During the preparation process, it is ensured that the nanoparticles can be evenly dispersed in the film layer. At the same time, in order to improve the cross-linking and curing degree of the film layer and improve the integrity of the film layer surface, a three-stage gradually increasing temperature curing process is adopted in the preparation process to slow down the curing rate of silicone as much as possible to ensure that the nanoparticles can be evenly dispersed in the cross-linking and curing of silicone.

[0061] Compared with the prior art, the present invention has at least the following beneficial effects:

[0062] (1) The double-resistance film layer of the NdFeB permanent magnet provided by the present invention is an organosiloxane super-hydrophobic coating doped with specific nanoparticles, which can effectively isolate water and oxygen from contacting the surface of the NdFeB substrate, so that the treated NdFeB permanent magnet has excellent corrosion resistance, and the film layer has excellent antibacterial properties, which can broaden the application range of the NdFeB permanent magnet and significantly extend the service life of the magnet;

[0063] (2) The preparation method provided by the present invention is suitable for batch surface treatment of NdFeB substrates of different sizes and shapes, and is easy to operate and environmentally friendly and pollution-free;

[0064] (3) In the preparation method provided by the present invention, the NdFeB substrate does not need to be chamfered in the early stage of surface treatment, which saves the cost of the chamfering process, effectively shortens the production process, and improves production efficiency;

[0065] (4) In the dual-resistance film layer of the NdFeB permanent magnet provided by the present invention, the nanoparticles are evenly distributed in the film layer, which plays a role of skeleton support, can improve the toughness of the single coating of organic siloxane, and effectively improve the impact resistance of the film layer on the surface of the magnet. DETAILED DESCRIPTION

[0066] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0067] Unless otherwise specified, some of the raw material information used in the examples and comparative examples of the present invention is as follows:

[0068] Polydimethylsiloxane: molecular weight 2000-3000;

[0069] Cyclomethicone: molecular weight 350-500;

[0070] Titanium dioxide nanomaterials: anatase nanoparticles, D50 is 350nm;

[0071] Zinc oxide nanoparticles: D50 is 200nm;

[0072] Cerium oxide nanoparticles: D50 is 200nm;

[0073] Alumina nanoparticles: D50 is 200 nm.

[0074] Example 1

[0075] In this embodiment, a NdFeB permanent magnet is provided, and the NdFeB permanent magnet comprises a NdFeB permanent magnet substrate and a dual-resistance film layer arranged on the surface of the NdFeB permanent magnet substrate;

[0076] The raw materials for preparing the dual-resistance film layer include organic siloxane, nanoparticles, and a curing agent;

[0077] Among them, the organosiloxane is a combination of polydimethylsiloxane and cyclopolydimethylsiloxane, and the mass ratio of the two is 2:1; the nanoparticles are a combination of titanium dioxide nanomaterials and zinc oxide nanoparticles, and the mass ratio of the two is 1.5:1; the curing agent is a combination of dihydrogen peroxide propylene, diphenylbutyl carbamate and diisopropylbenzene peroxide, and the mass ratio of the three is 4:2.5:1; based on the total mass of the raw materials for preparing the double-resistant film layer as 100%, the amount of nanoparticles is 3%, the total amount of organosiloxane and curing agent is 97%, and the mass ratio of organosiloxane to curing agent is 10:1.

[0078] The preparation method of the NdFeB permanent magnet comprises the following steps:

[0079] (1) Organic siloxane was added to a mixed solution of n-ethane and acetone (the volume ratio of the two was 1:1) and magnetically stirred at 200 rad / min for 1.5 h to obtain a first system (solid content of 70%), nanoparticles were added to the first system, magnetically stirred at 220 rad / min for 10 min and ultrasonicated at 65 kHz for 10 min to obtain a second system, and then a curing agent was added to the second system, and magnetically stirred at 190 rad / min for 0.5 h, and heated and baked at 50°C for 0.5 h to obtain an organic siloxane solution doped with nanoparticles.

[0080] (2) Place the NdFeB substrate (brand N40M, specification 10*10*0.75mm) in a 15wt% sodium hydroxide aqueous solution for ultrasonic degreasing for 15 minutes, then place the NdFeB substrate in 5wt% dilute nitric acid for pickling for 80 seconds, and ultrasonically clean it three times. Place the cleaned NdFeB substrate in an electric blast drying oven for drying, the drying time is 15 minutes, and the drying temperature is 80°C.

[0081] (3) using a spray coating method, the organic siloxane solution doped with nanoparticles prepared in step (1) is uniformly coated on the surface of the NdFeB permanent magnet substrate treated in step (2), and then cured in three stages to form a uniform dual-resistance film layer with a thickness of 10 μm;

[0082] The spray equipment parameters are set as follows: the distance between the spray gun and the product is 25 cm, the spray gun angle is 20°, the spray gun pressure is 110 Psi, and the gas used by the spray gun is air;

[0083] The three-stage curing is as follows: the first stage curing temperature is set to 60°C, and the curing time is 1.5h; the second stage curing temperature is set to 90°C, and the curing time is 1h; the third stage curing temperature is set to 100°C, and the curing time is 1h.

[0084] The NdFeB permanent magnet after solidification is turned over, and the NdFeB matrix is ​​sprayed and solidified again using the above process to obtain the NdFeB permanent magnet.

[0085] Example 2

[0086] The only difference between this embodiment and embodiment 1 is that the nanoparticles are a combination of titanium dioxide nanoparticles and cerium oxide nanoparticles, and the mass ratio of the nanoparticles is 2:1.

[0087] Example 3

[0088] The only difference between this embodiment and embodiment 1 is that the three-stage curing is as follows: the curing temperature of the first stage is set to 55°C, and the curing time is 1.5 hours; the curing temperature of the second stage is set to 85°C, and the curing time is 1 hour; the curing temperature of the third stage is set to 120°C, and the curing time is 1 hour.

[0089] Example 4

[0090] The only difference between this embodiment and embodiment 1 is that, based on the total mass of the raw materials for preparing the dual-resistance film layer being 100%, the amount of the nanoparticles used is 5%.

[0091] Example 5

[0092] The only difference between this embodiment and embodiment 1 is that, based on the total mass of the raw materials for preparing the dual-resistance film layer being 100%, the amount of the nanoparticles used is 1%.

[0093] Example 6

[0094] The difference between this embodiment and embodiment 1 is that cyclopolydimethylsiloxane is replaced by polydimethylsiloxane of equal mass, that is, the organosiloxane is only polydimethylsiloxane, and the three-stage curing conditions are changed at the same time. Specifically, the three-stage curing is as follows: the curing temperature of the first stage is set to 60°C, and the curing time is 2h; the curing temperature of the second stage is set to 90°C, and the curing time is 2h; the curing temperature of the third stage is set to 100°C, and the curing time is 1.5h.

[0095] Comparative Example 1

[0096] The only difference between this comparative example and Example 1 is that the nanoparticles are replaced with aluminum oxide nanoparticles of equal mass.

[0097] Comparative Example 2

[0098] The only difference between this comparative example and Example 1 is that the three-stage curing in step (3) of the preparation method is replaced by two-stage curing, specifically: the curing temperature of the first stage is set to 60°C, and the curing time is 1.5h; the curing temperature of the second stage is set to 100°C, and the curing time is 1h.

[0099] The dual-resistance film layer of the NdFeB permanent magnet provided in the embodiment and the comparative example was tested for performance, wherein 10 samples were randomly selected from each embodiment and the comparative example for testing, and the test results were averaged. The testing method is as follows:

[0100] (1) Salt spray test conditions: temperature 35±2℃, 50±5g / L NaCl, splash speed 1~2mL / 80cm 2 h, PH:6.5~7.2.

[0101] (2) PCT test (high pressure accelerated aging life test) conditions are: temperature: 120±2°C, 100% RH, absolute pressure: 0.1985 MPa.

[0102] (3) Antibacterial performance test conditions: Use PBS solution to dilute the E. coli solution to a concentration of 1*10 7 CFUml -1 , obtain the bacterial suspension, take 1 mL of the bacterial suspension and drop it on the surface of the double-antibody membrane layer, leave it at room temperature for 1 hour, and use the viable cell colony counting method to calculate the total number of surviving bacteria in the membrane layer.

[0103] The performance test results are shown in Table 1.

[0104] Table 1

[0105] Salt spray resistance test duration (h) PCT resistance test duration (h) Antimicrobial properties Example 1 500 160 99.37% Example 2 500 160 99.58% Example 3 480 150 99.32% Example 4 500 160 99.86% Example 5 500 150 80.25% Example 6 500 160 99.16% Comparative Example 1 500 140 33.72% Comparative Example 2 420 120 97.82%

[0106] It can be seen from Table 1 that the dual-resistance film layers of the NdFeB permanent magnets provided in Examples 1-4 of the present invention have excellent corrosion resistance (salt spray test duration: 480-500h, PCT test duration: 150-160h) and antibacterial properties (inhibition rate: 99.32%-99.86%).

[0107] Compared with Example 1, the antibacterial performance of the dual-resistance film layer of the NdFeB permanent magnet provided in Example 5 is significantly deteriorated; although the performance of the dual-resistance film layer of the NdFeB permanent magnet provided in Example 6 has not changed much, the curing time is 1.6 times that of Example 1, the production efficiency is reduced, and the dispersibility of the nanoparticles in the single organic silicone is worse than that of the example, so its antibacterial performance data is slightly worse.

[0108] Compared with Example 1, the antibacterial performance of the dual-resistance film layer of the NdFeB permanent magnet provided in Comparative Example 1 is significantly deteriorated; the corrosion resistance of the dual-resistance film layer of the NdFeB permanent magnet provided in Comparative Example 2 is significantly deteriorated, and the antibacterial performance is deteriorated.

[0109] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the NdFeB permanent magnet and its preparation method and use of the present invention, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A neodymium iron boron permanent magnet, characterized in that: The NdFeB permanent magnet comprises a NdFeB matrix and a dual-resistance film layer arranged on the surface of the NdFeB matrix; The raw materials for preparing the dual-resistance film layer include organic siloxane, nanoparticles, and a curing agent; The nanoparticles include any one of titanium dioxide nanoparticles, silver nanoparticles, silver-titanium dioxide composite nanoparticles, zinc oxide nanoparticles, and cerium oxide nanoparticles, or a combination of at least two of them.

2. The NdFeB permanent magnet according to claim 1, characterized in that: Based on the total mass of the raw materials for preparing the dual-resistance film layer being 100%, the amount of the nanoparticles used is 2% to 6%; Preferably, the mass ratio of the organosiloxane to the curing agent is (9-15):

1.

3. The NdFeB permanent magnet according to claim 1 or 2, characterized in that: The titanium dioxide nanoparticles are anatase nanoparticles; Preferably, the average particle size of the nanoparticles is 100-500 nm.

4. The NdFeB permanent magnet according to any one of claims 1 to 3, characterized in that: The organosiloxane includes at least two of polydimethylsiloxane, phenylmethyl-dimethylsiloxane, and cyclopolydimethylsiloxane; Preferably, the organosiloxane comprises a combination of polydimethylsiloxane and phenylmethyl-dimethylsiloxane in a mass ratio of 3:2 to 4:1, a combination of polydimethylsiloxane and cyclopolydimethylsiloxane in a mass ratio of 4:1 to 1:4, and a combination of cyclopolydimethylsiloxane and phenylmethyl-dimethylsiloxane in a mass ratio of 5:1 to 4:1; Preferably, the curing agent includes any one of diphenyl butyl carbamate, dihydropropane peroxide, diisopropylbenzene peroxide, ethoxylated trimethylolpropane triacrylate, and dibutyltin dilaurate, or a combination of at least two thereof; Preferably, the thickness of the dual-resistance film layer is 5 to 25 μm; Preferably, the salt spray resistance test duration of the dual-resistance film layer is ≥480h; Preferably, the high-voltage accelerated aging life test duration of the dual-resistance film layer is ≥150h; Preferably, the antibacterial rate of the dual-resistance film layer is greater than 99%.

5. A method for preparing a NdFeB permanent magnet as claimed in any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing organosiloxane, nanoparticles, a curing agent and an organic solvent, and heating to obtain a mixed solution; (2) coating the mixed solution on the surface of the NdFeB substrate and performing three-stage curing to obtain the NdFeB permanent magnet; The three-stage curing includes first stage curing, second stage curing, and third stage curing, wherein the temperature of the first stage curing is 50-70°C, and the curing time is 0.5-2h; the temperature of the second stage curing is 80-100°C, and the curing time is 0.5-2h; the temperature of the third stage curing is 100-140°C, and the curing time is 1-2h.

6. The preparation method according to claim 5, characterized in that: The organic solvent includes any one of acetone, n-ethane, n-heptane, methanol, and styrene, or a combination of at least two thereof; Preferably, the mixing in step (1) comprises first mixing the organosiloxane with the organic solvent for a first time to obtain a first system, then adding the nanoparticles to the first system for a second mixing to obtain a second system, and then adding the curing agent to the second system for a third mixing; Preferably, the heating temperature in step (1) is 40-50° C., and the heating time is 0.5-1 h.

7. The preparation method according to claim 5 or 6, characterized in that: The coating in step (2) comprises spraying; Preferably, the gas used for spraying includes air and / or nitrogen; Preferably, the angle range of the spray gun during the spraying is 15° to 40°; Preferably, the spraying distance is 25 to 35 cm; Preferably, the spraying pressure is 100-160 psi.

8. The preparation method according to any one of claims 5 to 7, characterized in that: Before the coating in step (2), the process also includes: sequentially degreasing, pickling and drying the surface of the NdFeB substrate.

9. The preparation method according to claim 8, characterized in that: The degreasing agent used in the degreasing treatment includes any one of sodium hydroxide, sodium carbonate, sodium bicarbonate or potassium hydroxide or a combination of at least two thereof; The degreasing treatment time is 3 to 15 minutes; The acid used for pickling includes any one of hydrochloric acid, nitric acid and sulfuric acid; The pickling time is 30 to 100 seconds; The drying temperature is 80-120°C.

10. A use of a NdFeB permanent magnet as claimed in any one of claims 1 to 4, characterized in that: The NdFeB permanent magnet is used in medical treatment, aerospace, transportation, household appliances or humanoid machines.